A new frontier of image guidance: Organs at risk avoidance with MRI‐guided respiratory‐gated intensity modulated radiotherapy: Technical note and report of a case. Issue 6 (4th May 2019) - Massaccesi, Mariangela; Cusumano, Davide; Boldrini, Luca; Dinapoli, Nicola; Fionda, Bruno; Teodoli, Stefania; Azario, Luigi; Mattiucci, Gian Carlo; Balducci, Mario; Cellini, Francesco; Valentini, Vincenzo
Abstract: The case of a 50‐year‐old man affected by a rhabdomiosarcoma metastatic lesion in the left flank Is reported. The patient was addressed to 50.4 Gy radiotherapy with concomitant chemotherapy in order to locally control the lesion. A Tri‐60‐Co magnetic resonance hybrid radiotherapy unit was used for treatment delivery and a respiratory gating protocol was applied for the different breathing phases (Free Breathing, Deep Inspiration Breath Hold and Final Expiration Breath Hold). Three intensity modulated radiation therapy (IMRT) plans were calculated and Final Expiration Breath Hold plan was finally selected due to the absence of PTV coverage differences and better organs at risk sparing (i.e. kidneys). This case report suggests that organs at risk avoidance with MRI‐guided respiratory‐gated Radiotherapy is feasible and particularly advantageous whenever sparing the organs at risk is of utmost dosimetric or clinical importance.